Seasonal changes in the physical performance of elite youth female soccer players - Emmonds, S.; Sawczuk, T.; Scantlebury, S.; Till, K.; Jones, B. (The Journal of Strength and Conditioning Research, 2020)
This study investigated the seasonal change in physical performance of 113 (Under 10: U10 [n = 20], U12 [n = 30], U14 [n = 31], and U16 [n = 32]) elite youth female soccer players. Players completed testing pre-, mid-, and post-season, including speed (10- and 30-m sprint), change of direction (CoD; 505 test), power (countermovement jump [CMJ]), strength (isometric midthigh pull), and aerobic capacity (Yo-Yo intermittent recovery test level 1 [YYIRL1]). A general linear model was used to evaluate the change in physical characteristics and the influence of covariates (baseline performance; change in maturity status) on each characteristic across the season. U10's speed and CoD performance decreased from pre-post season, whereas relative strength likely improved. U12's relative strength very likely improved; however, 10-m sprint performance decreased. Relative strength likely decreased, whereas 30-m sprint and CoD time very likely improved in U14's. U16's likely improved relative strength, CMJ, and 10-m sprint, and very likely improved 30-m sprint and CoD from pre-post season. U12-U16's improved YYIRL1 performance pre-post season. Strength and conditioning coaches working with U10-U12 players should look to develop speed, lower-body power, and CoD ability as part of structured strength and conditioning sessions as well as within warm-ups before pitch-based sessions. With U14-U16 players' manipulation of small-sided games combined with short-duration high-intensity running drills may provide an efficient training stimulus to develop the aerobic system while concurrently developing technical/tactical skills. Findings of this study provide a basis for the implementation of strategies to enhance the long-term athletic development of youth female soccer players.